Selection schemes of formation hollow parts with the taperid surface - A. V. Evstifeev; A. A. Alexandrov; V. V. Evstifeev (Вестник СибАДИ)
It describes different technologies obtained by cold forming of hollow parts with conical surfaces of solid and tubular billets, analyzed the advantages and disadvantages of certain methods of deformation. The results of mathematical modeling using a specialized system of finite-element Super Forge and the method of forming the upper assessment process hollow parts with internal conical surface. Conclusions on the possibility of reducing the forces of deformation due to changes in construction equipment.